2013
DOI: 10.1088/1748-9326/8/1/014040
|View full text |Cite
|
Sign up to set email alerts
|

Assessing climate change impacts on sorghum and millet yields in the Sudanian and Sahelian savannas of West Africa

Abstract: Sub-Saharan West Africa is a vulnerable region where a better quantification and understanding of the impact of climate change on crop yields is urgently needed. Here, we have applied the process-based crop model SARRA-H calibrated and validated over multi-year field trials and surveys at eight contrasting sites in terms of climate and agricultural practices in Senegal, Mali, Burkina Faso and Niger. The model gives a reasonable correlation with observed yields of sorghum and millet under a range of cultivars a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
217
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(235 citation statements)
references
References 36 publications
(41 reference statements)
12
217
2
4
Order By: Relevance
“…2). Higher temperatures accelerate plant phenology, leading to decreased yield potential (Schlenker and Lobell 2010;Sultan et al 2013). Temperatures above or below thresholds may trigger plant senescence, and reduce leaf area growth and photosynthesis.…”
Section: Effects On Mixed Farming Systemsmentioning
confidence: 99%
“…2). Higher temperatures accelerate plant phenology, leading to decreased yield potential (Schlenker and Lobell 2010;Sultan et al 2013). Temperatures above or below thresholds may trigger plant senescence, and reduce leaf area growth and photosynthesis.…”
Section: Effects On Mixed Farming Systemsmentioning
confidence: 99%
“…Although irrigation or timely availability of rainfall are capable of reducing heat-stress impacts, neither of these options is a regular feature in the arid regions where sorghum is a dominant crop. Furthermore, a comprehensive crop modeling exercise using data on sorghum and millets obtained from 35 stations across sub-Saharan West Africa (Senegal, Mali, Burkina Faso, and Niger) indicated that negative impacts associated with a 2°C temperature increase were not compensated by additional precipitation (19). Thus, even though sorghum might have some advantages relative to other crops for resisting extreme heat exposure, warming temperatures are still associated with large yield reductions in major growing regions, thereby suggesting an important need to investigate the potential for enhanced heat resilience.…”
mentioning
confidence: 99%
“…The rating process was operated on a nine-point scale and the relative importance of every two indices regarding the land suitability was compared. The weight coefficient of each crop was calculated by MATLAB software and its value ranged from 1 to 9/9 (Hoogenboom, 2000;Masilionytė and Maikštėnienė, 2011;Sultan et al, 2013;Tadross et al, 2009;Turner and Rao, 2013 (Table 4).…”
Section: Planting Ecological Adaptability Model Based On Gis-mcementioning
confidence: 99%